Is tea a healthy source of hydration?. Issue 3 (23rd August 2015) - Ruxton, C.; Phillips, F.; Bond, T.
Abstract: After water, tea is the most commonly consumed beverage worldwide, with over 80% of adults drinking tea in the UK. Lay concerns about caffeine have led to questions about the suitability of tea as a source of hydration. Several controlled trials have examined the effect of moderate caffeine consumption on fluid balance, from tea or other sources, concluding that intakes of up to 400 mg of caffeine, or six to eight servings of tea daily, are consistent with normal hydration. Unlike water, or other caffeinated beverages, tea is rich in flavonoids: plant compounds associated with health. There is now a growing body of evidence linking regular tea consumption with heart health, cognitive health, dental benefits and bodyweight management suggesting that tea may offer a healthy source of hydration. These studies are discussed in the context of typical tea intakes in the UK.